Popularization of a healthy lifestyle and prevention of diseases within the volunteer activity - E. I. Rubtsov; Sh. F. Juraeva; V. O. Petrova; A. A. Kholikova; R. V. Bobokalonov (Эндодонтия Today)
Dental morbidity is an acute and urgent problem among children and young people with disabilities. This category of the population is deprived of proper prevention and timely treatment. A volunteer movement, «DobroDent», has been created in the Ivanovo Region, promoting a healthy lifestyle and the prevention of dental diseases. The aim of the study was to optimize measures to increase the level of prevention of dental morbidity in children and adults, including those with disabilities (HIA). On the basis of specialized and general educational, medical institutions, the monitoring of the indicators of the oral cavity of 446 children and adolescents aged 12 and 15 years was carried out using subjective and objective methods recommended by ERO-FDI-WHO experts in dentistry. The insufficient level of dental education of children is confirmed by unsatisfactory indicators of dental status. Volunteers have sufficient information and technical resources to carry out their activities to stabilize the local dental situation.